Transmission of linezolid-resistant Enterococcus isolates carrying optrA and poxtA genes in slaughterhouses - Ni, Juan; Long, Xiaoqian; Wang, Mengmeng; Ma, Jiangang; Sun, Yangying; Wang, Wen; Yue, Min; Yang, Hua; Pan, Daodong; Tang, Biao (Frontiers in Sustainable Food Systems, 2023)
The presence of linezolid-resistant enterococci found in animal-derived food has attracted attention for possible transmission to human-derived enterococci through the food chain. Linezolid-resistant enterococci in farms have been widely reported, but enterococci carrying antimicrobial resistance (AMR) genes poxtA, optrA, or cfr(D) in slaughterhouse environments have not been well addressed. Here, 291 enterococci strains were isolated from 309 samples (94.17%) collected from two slaughterhouses in Hangzhou, China. The minimum inhibitory concentration (MIC) was determined using the microbroth dilution method, in which the highest rate of florfenicol resistance was 97.82% and the rate of multidrug resistance (MDR) was 95.65%. A total of 4 poxtA-positive enterococci and 42 optrA-positive enterococci were identified based on PCR. Two strains carried multiple linezolid resistance genes, among which Enterococcus casseliflavus CQFYY22-063 cocarrying optrA, poxtA and cfr(D) was isolated from the duck cecum, and Enterococcus faecium CQFYH22-006 cocarrying optrA and poxtA was isolated from slaughterhouse sewage for the first time. Furthermore, Oxford Nanopore Technology revealed that the optrA gene of strain CQFYY22-063 was located on the Inc18-type plasmid pFYY063-optrA-70K, and the poxtA and cfr(D) genes were located on the Inc18-type plasmid pFYY063-poxtA-12K. Meanwhile, the poxtA gene of strain CQFYH22-006 was located on the Rep3-type plasmid pFYH006-poxtA-25K, and the optrA gene was located on the chromosome. Together, linezolid resistance in slaughterhouses deserves extensive attention, indicating the need to strengthen the monitoring of different links in the food production chain within the One Health concept.